Uma Análise dos impactos da privatização da Light sob o enfoque da agência reguladora e do consumidor - Ferreira, Luís Fernando Filardi (2000)
The objective of this work is identify the impacts of the Light privatization under the consumer point of view, with special focus to the service's quality, verifying the channels introduced by Light to measure the consumer satifaction and evaluate how the consumers interests have influence on the company's decisions. This study also objective to identify the main challenges faced by the Regulatory Agency and the Brazilian State on the new relationship model implementation STATE - CONSUMER - CONCESSIONARY, propoused to the energy sector after the privatization. A descriptive methodology is used to identify the most significant changes on the Light's trasition process to the private administration, followed by an explicative investigation to find how the consumer has passed throught this change, based on bibliographical research and interviews. The obtained conclusions shows that the impacts of the Light privatization under the consumer point of view are positive and highlights that the Regulatory Agency has to have the power and autonomy to control and advice the conncessionaries, building consulte and evaluation mechanisms to activate the consumer participation.